P51 Simulation to tackle never events- utilising video as educational tool at northern lincolnshire and goole NHS trust NLaG. (3rd November 2019) - Quayle, Alexandra; Harrison, Nick; McGuffie, Rochelle
Abstract : Background: A nerve block performed on the incorrect side is classified as a Never event. 1 As part of the 5 steps to safer surgery 'Stop Before You Block' has been incorporated into the WHO check list before the start of any operative procedure. The Development and Simulation Hub, (DaSH) working with Risk and Governance assessed the root cause analyses of two wrong side nerve blocks which had occurred in the last 5 years, examining all the contributing factors, in order to produce a widely accessible training package to prevent this reoccurring. Method: Utilising theatre staff and a simulated patient, we recreated an exact simulation of a patient's journey undergoing a Total Knee Replacement, using authentic theatre equipment, paperwork and in real time. The simulation specifically included all the latent errors and contributing factors which led to the wrong side femoral nerve block. The simulation was filmed and an educational video was created with participants' consent. In order to emphasise the learning points the video includes a team debrief specifically highlighting the multiple factors which led to the error, and nearly wrong side surgery. The discussion reiterates how the patient's journey and all checks should be conducted correctly. Is also focusses on the major impact of human factors in this incident. Results: Contributory factors included: Covering of marked knee with thromboembolic stocking Stocking applied to incorrect leg Inexperienced ward staff at theatre handover Interruptions during handover, with change of staff 6th patient on list Automatic application of tourniquet, and prepping of femoral area Failure to stop before block The video is being shown at medical staff educational and audit and governance meetings across all three trust sites. Theatre educators are ensuring wider rolling out across the theatre teams. Conclusion and recommendations: In situ simulation is an excellent method of learning for healthcare professionals, however only staff involved benefit from the learning experience. A video of a recreated simulation of a real clinical incident is a powerful method of sharing the lessons learnt, and has access to a much wider audience, and repeat use, re-emphasising the lessons and for new theatre staff and rotating medical staff. References: NHS Improvement (January 2018) Never Events List. London NHS Improvement https://patientsafety.health.org.uk/resources/human-factor-learning-ginas-story